Assessment of Needs in Children Suffering From Refractory Non-neurogenic Urinary and Fecal Incontinence and Their Caregivers' Needs and Attitudes Toward Alternative Therapies (SNM, TENS) - Dos Santos, Joana; Marcon, Edyta; Pokarowski, Martha; Vali, Reza; Raveendran, Lucshman; O'Kelly, Fardod; Amirabadi, Afsaneh; Elterman, Dean; Foty, Richard; Lorenzo, Armando; Koyle, Martin (Frontiers in Pediatrics, 2020)
Background: Non-neurogenic urinary and fecal incontinence (UI, FI) affects approximately 6% of North American children with 1% of cases becoming refractory (nonresponsive to standard therapies). Incontinence has major potential long-term physiological and psychological implications for patients and their families. While Sacral Neuromodulation (SNM) and Transcutaneous Nerve Stimulation (TENS) are alternative therapies available for the treatment of refractory UI/FI, these are not approved for use in children in Canada. The present study assessed participants’ perception of current treatments, incontinence burden, and attitudes towards novel therapies in a single pediatric institution. Methods: Multiple validated questionnaires including Dysfunctional Voiding Scoring System (DVSS), Bristol Stool Chart (BSC), Pediatric Incontinence measurement (PinQ), and Time-Driven Activity Based Costing were used to perform a needs assessment for patients with non-neurogenic refractory incontinence, and to determine patients’ and caregivers’ attitudes towards alternative therapies. Results: 75% of patients and 89% of caregivers reported a moderate to severe impact of incontinence on QoL with diminished social interactions among the primary concerns. Caregivers were frustrated with current treatments and were open to trying alternative therapies (SNM and TENS), which, at least in the case of SNM, seems to be less expensive, possibly less burdensome and more effective than current surgical options. Conclusion: Pediatric refractory UI/FI has a large impact on patients’ and caregivers’ QoL and alternative therapies with the potential to improve QoL of patients and caregivers should be further investigated as a substitute for surgery.